Prevalence of cytopenia and its associated factors among HIV infected adults on highly active antiretroviral therapy at Mehal Meda Hospital, North Shewa Zone, Ethiopia - Angesom Gebreweld; Temesgen Fiseha; Nibret Girma; Haftay Haileslasie; Daniel Gebretsadik; Benn Sartorius (PLoS ONE, 2020)
Background Cytopenias affect the outcomes of highly active anti-retroviral therapy that results in higher morbidity, mortality, and impaired quality of life. The purpose of this study was to assess the prevalence of cytopenia and its associated factors among HIV infected adults on highly active antiretroviral therapy at Mehal Meda Hospital, North Shewa Zone, Ethiopia. Method A cross-sectional health facility based study was conducted among 499 consecutively selected adult HIV infected patients taking HAART for at least six months from January to April 2018. The study participant’s socio-demographic and clinical information was collected using a pre-tested questionnaire and reviewing of medical records by trained clinical nurses. Complete blood count and CD4 T cell count were determined by Sysmex KX-21 N and BD FACS count respectively. Bivariate and multivariate analysis was performed to identify the independently associated factors of cytopenia and prevalence ratios and their 95% confidence intervals were estimated using Poisson regression model with robust error variance to quantify the strength of statistical association. In all cases, a P value less than 0.05 was considered statistically significant. Result Out of the total study participants, 39.9% had at least one form of cytopenia, 23.2% had anemia, 13.8% had leukopenia, 12.4% had thrombocytopenia, 11.62% had bi-cytopenias, and only 1% had pancytopenia. In multivariate analysis, cytopenia was independently associated with older age groups, male gender, ZDV based regimen, and CD4 count less than 200 cells/mm3. Conclusions In this study, the magnitude of any cytopenia was 40% among adult HIV infected patients taking highly active antiretroviral therapy and the prevalence increased as the CD4 count decreases. Therefore, these warrant the need for monitoring hematological parameters of HIV infected patients on HAART to reduce morbidity and mortality.